The Influence of Financial Knowledge and Financial Experience on Financial Satisfaction with Financial Literacy as Intervening Variables in Generation Z in the Air Batu District - Siregar, Qahfi Romula; Simatupang, Jumeida (AIBPM Publisher, 2023)
This study aims to find out how the influence of Financial Knowledge and Financial Experience on Financial Satisfaction with Financial Literacy as an Intervening Variable in Generation Z in Air Batu District. The population in this study were all Z generations in Air Batu District and the sample was 100 people. Data analysis and uses the Partial Least Square (PLS) model. The results show that Financial Knowledge has a significant effect on Financial Satisfaction, Financial Experience has a significant effect on Financial Satisfaction, Financial Knowledge has a significant effect on Financial Literacy, Financial Experience has a significant effect on Financial Literacy, Financial Literacy has a significant effect on Financial Satisfaction, Financial Knowledge has a significant effect on Financial Satisfaction through Financial Literacy as an intervening variable. Financial Experience has a significant effect on Financial Satisfaction through Financial Literacy as an intervening variable.